1993
DOI: 10.1128/aem.59.11.3946-3950.1993
|View full text |Cite
|
Sign up to set email alerts
|

Temporal expression of the major lignin peroxidase genes of Phanerochaete chrysosporium

Abstract: DNA probes specific for the genes encoding major lignin peroxidase (LIP) isozymes H2, H8, and H10 of Phanerochaete chrysosporium were constructed. These probes were used to study the temporal expression of the three lip genes in defined low-nitrogen medium. H2 gene transcripts were produced at high levels on days 4, 5, and 7 and at low levels on day 6, while the H8 gene transcripts peaked on day 4 and were produced in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…However, we have shown that PCR of cDNA preparations can be used for more sensitive analysis that also allows the resolution of genes coding for isozymes (4). This is important since it has been shown that there are gene families with differential gene expression (2,4,9,21,33,34,43,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have shown that PCR of cDNA preparations can be used for more sensitive analysis that also allows the resolution of genes coding for isozymes (4). This is important since it has been shown that there are gene families with differential gene expression (2,4,9,21,33,34,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that for both LiPs and MnPs there are families of genes which are differentially expressed (2,4,33,35,43). Cellobiohydrolases have been characterized and show synergy (46), and whereas a complex family of CBHI-encoding genes showing differential expression exists (8,9,41), only a single CBHII-encoding gene exists (44).…”
mentioning
confidence: 99%
“…Information regarding enzyme expression in white-rot fungi has mostly been obtained from cultures grown in chemically defined liquid media; extensive data concerning LiP isozyme profiles have been gathered from liquid cultures at the level both of protein (5,8,12,30) and of mRNA transcripts (4,5,38,49). Very little data exist for white-rot fungi grown on solid substrates.…”
mentioning
confidence: 99%
“…However, this is not the case; in contrast to the LiP H8-encoding genes discussed above, those for H2 can be strongly expressed in N sufficiency (Holzbaur and Tien, 1988;Stewart et al, 1992;Dosoretz et al, 1993). lig5, encoding an H2-like isoenzyme in strain ME446, is expressed when both N and C are limited (James et al, 1992;Brooks et al, 1993;Broda et al, 1995), and CLG4, the equivalent gene in strain BKM-F-1767, is expressed when only N is limited (Boominathan et al, 1993). Together, these studies show that among the lip genes those encoding the H2 proteins are expressed under the widest variety of conditions and ages of culture and from the earliest time points.…”
Section: Lignocellulolytic Gene Expression: Peroxidasesmentioning
confidence: 91%